Role of melatonin in periodontal disease - A systematic review - S Swarna Meenakshi; Sankari Malaiappan (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Melatonin is an indolamine that is primarily secreted by the pineal gland. It has immunomodulatory as well as antioxidant properties. It is a potent anti-oxidant that protects against inflammation and cellular damage caused by reactive oxygen species, also has potent angiogenic function that adds on to the benefits of melatonin. As a result of these actions, melatonin may be useful as an adjuvant in the treatment of various conditions in the oral cavity. The aim of this study is to systematically evaluate the role of melatonin in periodontal disease. Methods: An extensive review of the scientific literature was carried out using PubMed, Science Direct, Google Scholar and the Cochrane base. Research articles were collected upto December 2017. Results: Melatonin may have beneficial effects in certain inflammatory oral pathologies, mainly periodontal diseases where they inhibit bone resorption destroy reactive oxygen species, stimulates osteoblastic differentiation. Salivary melatonin could also act as a risk indicator for periodontal diseases. Conclusion: Many studies showed that the melatonin levels in GCF, Saliva, Serum of patients suffering from chronic periodontitis is lowered suggesting that may play a pivotal role in protecting the tissue from damage caused by oxidative stress. However, there exists no data on the concentration needed, method of application for potential benefits. Randomized clinical trials in this field are needed to fill the lacunae and better improve our understanding.